2009
DOI: 10.1016/j.nlm.2008.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Sensory memory consolidation observed: Increased specificity of detail over days

Abstract: Memories are usually multidimensional, including contents such as sensory details, motivational state and emotional overtones. Memory contents generally change over time, most often reported as a loss in the specificity of detail. To study the temporal changes in the sensory contents of associative memory without motivational and emotional contents, we induced memory for acoustic frequency by pairing a tone with stimulation of the cholinergic nucleus basalis. Adult male rats were first tested for behavioral re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 58 publications
(75 reference statements)
0
27
0
Order By: Relevance
“…Previous studies reported that catalpol increased the hippocampal neuroplasticity in the aged rats [52] and attenuated MPTP-induced neuronal degeneration of nigral-striatal dopaminergic pathway in mice [53] partly attributed to BDNF upregulation. At the same time, higher BDNF level, together with ACh, is beneficial to brain plasticity and the induction of specific, associative detail behavioral memory [54, 55] and synaptogenesis [56]. In line with previous studies, our results showed that catalpol can upregulate BDNF level and here existed the strong positive correlation between the ACh level and the BDNF level in the hippocampus ( r = 0.859, P < 0.01), which are together beneficial to memory improvement and to explain from another side why catalpol ameliorated memory impairments in the SCOP-induced amnesic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that catalpol increased the hippocampal neuroplasticity in the aged rats [52] and attenuated MPTP-induced neuronal degeneration of nigral-striatal dopaminergic pathway in mice [53] partly attributed to BDNF upregulation. At the same time, higher BDNF level, together with ACh, is beneficial to brain plasticity and the induction of specific, associative detail behavioral memory [54, 55] and synaptogenesis [56]. In line with previous studies, our results showed that catalpol can upregulate BDNF level and here existed the strong positive correlation between the ACh level and the BDNF level in the hippocampus ( r = 0.859, P < 0.01), which are together beneficial to memory improvement and to explain from another side why catalpol ameliorated memory impairments in the SCOP-induced amnesic mice.…”
Section: Discussionmentioning
confidence: 99%
“…The transitory inability to display stimulus specificity could be confounded with generalization. In addition, recent experiments in mammals have shown that stimulus specificity can increase with time after training (Weinberger et al, 2009). For these reasons, in the present study the attributes of the behavioral memory were evaluated in test trials performed 24 h after training.…”
Section: Methodsmentioning
confidence: 99%
“…The materials and methods were mainly identical to those previously reported (Weinberger, Miasnikov, & Chen, 2009), and will be described only briefly. All procedures were performed in accordance with the University of California Irvine Animal Research Committee and the NIH Animal Welfare guidelines.…”
Section: Methodsmentioning
confidence: 99%